The Many Faces of Socioeconomic Change - Toye, John (Oxford University Press, 2017)
This book provides a survey of different ways in which economic sociocultural and political aspects of human progress have been studied since the time of Adam Smith. Inevitably, over such a long time span, it has been necessary to concentrate on highlighting the most significant contributions, rather than attempting an exhaustive treatment. The aim has been to bring into focus an outline of the main long-term changes in the way that socioeconomic development has been envisaged. The argument presented is that the idea of socioeconomic development emerged with the creation of grand evolutionary sequences of social progress that were the products of Enlightenment and mid-Victorian thinkers. By the middle of the twentieth century, when interest in the accelerating development gave the topic a new impetus, its scope narrowed to a set of economically based strategies. After 1960, however, faith in such strategies began to wane, in the face of indifferent results and general faltering of confidence in economists' boasts of scientific expertise. In the twenty-first century, development research is being pursued using a research method that generates disconnected results. As a result, it seems unlikely that any grand narrative will be created in the future and that neo-liberalism will be the last of this particular kind of socioeconomic theory.